(3EJMGa Pi GdeQhAI hGdCfGaI HeG LGA aj GdUObI hGdVjGaIs - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ENJU ef TGA ef YHGOgCeG HYO , aGfg deG MUd ai HdGO HLjdI hZjQgG ef CWQGa Gdjef hGdMLGR bMW YGe s
(3BNQgG (B:s
(3Yf CfS QVi Gddg Yfg Gfg Udi Gddg Ydjg hSde bGd (B: (3cGO GdabQ Cf jchf caQkG Cf GdMeO ddg QH GdYGdejf aQZJ ef JCdjaI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3HChdgG Jedc SfI (B1201(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B152s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa eLehYI GHf SYd (B((3eLehY (B- (3JQje (B412) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs